TANJUNG PINANG CITY GOVERNMENT’S EFFORTS TO IMPROVE CIVIL SERVANT PERFOMANCE DISCIPLINE DURING THE COVID-19 PANDEMIC (CASE STUDY OF THE TANJUNG PINANG BKPSDM) - RIZKY ANANDA, BALQIS (RADJA PUBLIKA, 2022)
This research aims to examine the influence of transformational Pandemic Covid-19 on employee performance in the Tanjungpinang City Government with a mentality of being ready to change as a mediator. The data were collected through simple random sampling technique and the results of a questionnaire that returned and were valid for 50 samples. The data were processed by the SEM method using SmartPLS 3.0 software. From the results of this research, it is concluded that Pandemic Covid-19 has no significant effect on employee performance, but transformational Pandemic Covid-19 has a significant and positive effect on the mentality of being ready to change as a mediator. This research also concludes that a mentality of being ready to change has a significant and positive effect on the relationship between transformational Pandemic Covid-19 and employee performance. The mentality ready to change in this study serves as a full mediator. This new research proposes a model for building employee performance among Tanjungpinang City Government through the development of transformational Kepemimpinan practices with a change-ready mentality as a mediating variable. This research can pave the way for developing a ready-to-change mentality in employees and get finished all the jobs.